Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1074/jbc.m510700200
|View full text |Cite
|
Sign up to set email alerts
|

The Interleukin-1β Gene Is Transcribed from a Poised Promoter Architecture in Monocytes

Abstract: Cytokine transcription is usually regulated by transcription factor binding and chromatin remodeling following an inducing signal. By contrast, these data showed the interleukin (IL)-1␤ promoter assembles into a "poised" structure, as evidenced by nuclease accessibility and loss of core histones immediately surrounding the transcription start site. Strikingly, these properties do not change upon transcriptional activation by lipopolysaccharide. Furthermore, association of two key transcriptional activators, PU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
86
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(98 citation statements)
references
References 63 publications
(63 reference statements)
12
86
0
Order By: Relevance
“…This function is necessary for maximal activity of some chromatin embedded genes (Kowenz-Leutz and Leutz, 1999). The role for chromatin remodeling for IL1B is interesting because monocytic cell types appear to have an open chromatin at the promoter with Spi-1 bound and poised for action (Liang et al, 2006). However, in HeLa S3 cells, endogenous IL1B is inactive, suggesting it has a more compact structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This function is necessary for maximal activity of some chromatin embedded genes (Kowenz-Leutz and Leutz, 1999). The role for chromatin remodeling for IL1B is interesting because monocytic cell types appear to have an open chromatin at the promoter with Spi-1 bound and poised for action (Liang et al, 2006). However, in HeLa S3 cells, endogenous IL1B is inactive, suggesting it has a more compact structure.…”
Section: Discussionmentioning
confidence: 99%
“…The promoter functionally couples to a far-upstream enhancer via a mechanism that likely involves a cooperative long-range interaction between Spi-1 and C/EBPβ (Kominato et al, 1995;Listman et al, 2005;Yang et al, 2000). Chromatin remodeling has also been implicated in IL1B regulation as others have shown an open promoter conformation in myeloid cell lines (Liang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In resting monocytes and macrophages, the IL-1b promoter is packaged into a nucleosome-free, highly accessible chromatin structure that remains largely unchanged upon stimulation, whereas the IL-1b promoter is inaccessible in undifferentiated promyeloid cells, as well as in primary B and T cells (6,34,42). Moreover, several transcription factors, including IRF8, Pu.1, nonphosphorylated STAT1, and C/EBPb, were described to be constitutively bound to the IL-1b promoter and/or enhancer elements, enabling rapid gene transcription upon cellular activation (6,34,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several transcription factors, including IRF8, Pu.1, nonphosphorylated STAT1, and C/EBPb, were described to be constitutively bound to the IL-1b promoter and/or enhancer elements, enabling rapid gene transcription upon cellular activation (6,34,(43)(44)(45). Recruitment of NF-kB is one of the crucial steps for initiating IL-1b transcription after stimulation (4)(5)(6)46).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown C/EBPb binds the IL1b promoter at -17 and -107 and also -168 and -258. 16 We thus identify a new binding site further upstream and demonstrate for the first time that the C/EBPb2 isoform can bind to the IL1b promoter. ChIP was also used to investigate 5,000 base pairs upstream and downstream of the transcriptional start site of IL1R2 and IL1RL1, but C/EBPb2 was not found to bind anywhere within these regions, suggesting either C/EBPb2 regulation is indirect or accomplished over a longer distance.…”
Section: Genomic Profiling Of C/ebpb2 Transformed Mammary Epithelial mentioning
confidence: 99%